Semi-interpenetrating dual-network organogel OCA optical adhesive applied to folding display equipment, preparation method of semi-interpenetrating dual-network organogel OCA optical adhesive and folding display equipment
By using semi-interpenetrating dual-network organic gel OCA optical glue in folding display equipment, combining crosslinked and non-crosslinked network components and polar small molecules, the bonding and folding resistance of traditional optical glue in folding equipment is solved. The problem of insufficient results enables high light transmittance and excellent bending resistance.
Patent Information
- Application Number
- CN202411540731.5
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-10-31
- Publication Date
- 2025-01-03
- Estimated Expiration
- 2044-10-31
AI Technical Summary
Traditional optical pressure-sensitive adhesives are difficult to take into account both bonding and folding resistance in folding display equipment, and are prone to irreversible deformation and debonding and glue disassembly after multiple folding.
The preparation method of semi-interpenetrating dual network organic gel OCA optical glue is adopted. Through the combination of cross-linking network components and non-crosslinking network components, polar small molecules are introduced to form semi-interpenetrating dual network structure, providing skeleton support and Reversible hydrogen bonding to improve creep resistance and energy dissipation.
It significantly improves the creep and fatigue resistance of optical glue, ensures the elasticity and peel strength during folding process, has high light transmittance and low haze, and can withstand more than 200,000 consecutive bending resistance. Suitable for folding display devices.
Smart Images

Figure CN119242226A_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to the technical field of optical adhesives, and in particular to a semi-interpenetrating double network organic gel (OCA) optical adhesive applied to a folding display device, a preparation method thereof, and a folding display device. Background Art
[0002] As the hyperconnected society develops, people interact with each other in the network, and people and objects interact through display services. Display technology continues to evolve and improve to consider user convenience. Organic light-emitting diode technology has promoted the application of new foldable and flexible screens. Compared with rigid flat displays, these innovative displays are suitable for wearable devices, foldable smartphones, medical sensors and other fields.
[0003] Pressure-sensitive adhesives are used to effectively combine highly transparent and viscoelastic covering layers (such as cover glass and touch sensors) with various display layers. With the continuous advancement of display technology, display layers are gradually showing foldable characteristics, so pressure-sensitive adhesives also need to have corresponding properties. When the display layer is folded, it will be subjected to tensile and compressive stresses at the same time. If the strain cannot be recovered quickly, the adhesive may sag and swell, and this residual strain will cause the adhesive to break and peel. Pressure-sensitive adhesives can adjust the neutral plane during the folding process while connecting various folding display layers. Flexible adhesives can form partitions between brittle substrates, thereby reducing the stress applied to the material during deformation, effectively preventing problems such as warping, delamination and failure. In addition, residual stress relaxation properties help protect adhesives from cracking and rapid fatigue failure.
[0004] The low cohesive strength of the traditional linear polymer structure of polyacrylates (PSAs) causes the polymer chains to unwind irreversibly and be difficult to fully recover. Although crosslinking can improve the recoverability of the polymer, it is also necessary to balance the relationship between its recovery ability and bonding strength. Crosslinking can increase the internal connectivity and recyclability of polyacrylates, but it will reduce the mobility of the polymer chains and thus affect the bonding strength. In addition, crosslinking also limits the ability of polymer chains to rearrange, further reducing the stress relaxation performance.
[0005] In order to maintain a certain peel strength, traditional optical pressure-sensitive adhesives often have a low cross-linking density, which makes the optical adhesive unable to cope with the multiple folding or long-term bending of folding display devices, and is prone to irreversible creep, leading to debonding and cracking.
[0006] Chinese invention patent CN110776855B discloses a UV light-curing high-transmittance optical adhesive and its preparation method. In terms of weight, the raw material formula of the high-transmittance optical transparent adhesive includes 20-50 parts of (meth) alkyl acrylate, 15-40 parts of (meth) hydroxyalkyl acrylate, 10-15 parts of N-atom-containing polar monomer, 10-20 parts of active diluent, 0.1-2 parts of chain transfer agent, 0.5-1 parts of thermal initiator, 0.5-1 parts of photoinitiator, and 0.6-1.8 parts of other additives. The obtained product has the advantages of high transmittance and low haze. However, its modulus is relatively high, and its creep resistance is poor. It is easy to produce irreversible deformation after multiple folding, which leads to bonding failure.
[0007] Chinese invention patent application CN113025240A provides a UV solvent-free optical adhesive and a preparation method thereof, comprising 50-95 parts of alkyl acrylate, 1-30 parts of acrylate with aliphatic cyclic side chains, 1-30 parts of acrylate with polar cyclic side chains, 1-30 parts of acrylate containing polar groups, 0.01-5 parts of multifunctional acrylate, and 0.02-2.0 parts of photoinitiator. By introducing polar cyclic structures and non-polar cyclic structures for molecular design, the compatibility of the polar and non-polar parts in the polymer chain segments is enhanced while controlling the glass transition temperature of the material, thereby improving the optical properties of the optically transparent adhesive film, high temperature and high humidity resistance, and water boiling whitening properties, and having good ink filling performance and easy rework. However, this patent cannot effectively cope with the stress generated during multiple folding, so its folding performance is lacking, and its light transmittance is only 92%, which is poor in light transmittance. Summary of the invention
[0008] In order to overcome the above-mentioned shortcomings and deficiencies of the prior art, the purpose of the present invention is to provide a method for preparing a semi-interpenetrating double network organic gel OCA optical adhesive for use in folding display devices, thereby effectively solving the problem that traditional optical pressure-sensitive adhesives cannot take into account both bonding performance and folding resistance.
[0009] Another object of the present invention is to provide a semi-interpenetrating double network organic gel OCA optical adhesive for use in folding display devices.
[0010] Another object of the present invention is to provide a foldable display device.
[0011] The purpose of the present invention is achieved through the following technical solutions:
[0012] The present invention provides a method for preparing a semi-interpenetrating double network organic gel (OCA) optical adhesive for a foldable display device, comprising the following steps:
[0013] Preparation of a cross-linked network component: 20 to 80 parts of an alkyl acrylate monomer, 5 to 20 parts of an acrylic acid monomer with a carboxyl group, 0.05 to 1 part of a cross-linking agent, 0.1 to 2 parts of a thermal initiator, and 90 to 240 parts of a solvent are added to a reaction container, the temperature is raised to 70 to 75° C., and the reaction is carried out at a speed of 70 to 80 r / min for 6 to 8 hours; after the reaction is completed, the temperature is lowered to room temperature and the material is discharged to obtain a cross-linked network component;
[0014] Preparation of non-crosslinked network components: 20-80 parts of alkyl acrylate monomers, 5-20 parts of hydroxy acrylate monomers, 0.1-2 parts of thermal initiators, and 0.5-1 parts of chain transfer agents are added to a reaction container, heated to 70-75° C., and reacted at a speed of 70-80 r / min for 6-8 hours; after the reaction is completed, the reaction is cooled to room temperature and discharged to obtain a non-crosslinked network component;
[0015] Preparation of semi-interpenetrating double network organogel: 20 to 40 parts of cross-linked network components, 20 to 40 parts of non-cross-linked network components and 1 to 40 parts of polar small molecules are mixed evenly and then coated on a release film, and then placed in an oven and dried at 60 to 80° C. to obtain a semi-interpenetrating double network organogel OCA optical adhesive;
[0016] The polar small molecule is at least one of ethanol, n-propanol, isopropanol, n-butanol, isobutanol, n-pentanol, isopentanol, n-hexanol, heptanol, octanol, isooctyl alcohol, ethylene glycol, propylene glycol, butanediol, pentanediol, hexanediol, heptanediol, octanediol, glycerol, pentaerythritol, polyethylene glycol, and polypropylene glycol.
[0017] Preferably, the alkyl acrylate is at least one of methyl acrylate, ethyl acrylate, isopropyl acrylate, isoamyl acrylate, sec-butyl acrylate, n-butyl acrylate, isobornyl acrylate, 2-methylbutyl acrylate, 4-methyl-2-pentyl acrylate, 2-ethylhexyl acrylate, and isooctyl acrylate.
[0018] Preferably, the carboxyl-containing acrylic monomer is at least one of acrylic acid, methacrylic acid, and 2-carboxyethyl acrylate.
[0019] Preferably, the crosslinking agent is at least one of aluminum acetylacetonate, aziridine, ethylene glycol di(meth)acrylate, diethylene glycol di(meth)acrylate, triethylene glycol di(meth)acrylate, tetraethylene glycol di(meth)acrylate, 1,4-butanediol di(meth)acrylate, 1,6-hexanediol di(meth)acrylate, 1,6-hexanediol diacrylate, trimethylolpropane triacrylate, dipropylene glycol diacrylate, tripropylene glycol diacrylate, cyclohexanedimethanol di(meth)acrylate, alkoxylated cyclohexanedimethanol diacrylate, ethoxylated bisphenol A di(meth)acrylate, neopentyl glycol diacrylate, polyethylene glycol di(meth)acrylate, polypropylene glycol di(meth)acrylate and urethane di(meth)acrylate.
[0020] Preferably, the thermal initiator is at least one of benzoyl peroxide or azobisisobutyronitrile.
[0021] Preferably, the hydroxy acrylate is at least one of hydroxyethyl acrylate, hydroxypropyl acrylate, hydroxyethyl methacrylate and hydroxypropyl methacrylate.
[0022] Preferably, the chain transfer agent is at least one of dodecyl mercaptan and tert-dodecyl mercaptan.
[0023] Preferably, the solvent is at least one of acetone, ethyl acetate, n-butyl acetate, n-hexane, n-heptane, benzene, toluene, methyl ethyl ketone, methyl isobutyl ketone, cyclohexane, methylcyclohexane, and anhydrous ethanol.
[0024] The present invention also provides a semi-interpenetrating double network organic gel OCA optical adhesive for folding display devices, comprising a mixture coated on a release film; the mixture comprises 20 to 40 parts of a cross-linked network component, 20 to 40 parts of a non-cross-linked network component and 1 to 40 parts of a polar small molecule;
[0025] The cross-linked network component is prepared by reacting 20 to 80 parts of alkyl acrylate monomer, 5 to 20 parts of acrylic acid monomer with carboxyl group, 0.05 to 1 part of cross-linking agent, 0.1 to 2 parts of thermal initiator and 90 to 240 parts of solvent;
[0026] The non-crosslinked network component comprises 20 to 80 parts of alkyl acrylate monomers, 5 to 20 parts of hydroxy acrylate monomers, 0.1 to 2 parts of thermal initiator, and 0.5 to 1 part of chain transfer agent;
[0027] The polar small molecule is at least one of ethanol, n-propanol, isopropanol, n-butanol, isobutanol, n-pentanol, isopentanol, n-hexanol, heptanol, octanol, isooctyl alcohol, ethylene glycol, propylene glycol, butanediol, pentanediol, hexanediol, heptanediol, octanediol, glycerol, pentaerythritol, polyethylene glycol, and polypropylene glycol.
[0028] The present invention also provides a folding display device, comprising the semi-interpenetrating double network organic gel OCA optical adhesive.
[0029] Compared with the prior art, the present invention has the following advantages and beneficial effects:
[0030] (1) The semi-interpenetrating double network organogel OCA optical adhesive used in the folding display device of the present invention has a cross-linked network component as a skeleton in the colloid, which can improve the cohesive energy of the optical adhesive and thus enhance the creep resistance, and can provide an effective skeleton support to prevent the colloid from undergoing irreversible deformation when folded, thereby ensuring that the colloid has good resilience and excellent fatigue resistance during the folding process; the uncross-linked network components are almost all linear macromolecules, which can improve the wettability of the colloid and thus improve the peel strength of the optical adhesive and enhance the bonding with the substrate.
[0031] (2) The semi-interpenetrating double network organic gel OCA optical adhesive used in the folding display device of the present invention introduces polar small molecules, which enhances the polarity of the substrate and forms a large number of reversible hydrogen bonds between the molecules. These reversible hydrogen bonds can absorb a large amount of energy in the process of being destroyed and rebuilt, providing the colloid with good energy dissipation capacity, further reducing the generation of folding stress, thereby greatly improving the bending resistance of the optical adhesive; and the small molecules are beneficial to reducing the glass transition temperature and elastic modulus of the colloid, further enhancing the flexibility of the colloid.
[0032] (3) The semi-interpenetrating double network organic gel OCA optical adhesive used in folding display devices of the present invention has a transmittance greater than 99%, a haze value not exceeding 0.1%, excellent optical properties, moderate initial adhesion and peeling force, and continuous bending resistance of more than 200,000 times, and can be widely used in the bonding of devices in folding display devices. BRIEF DESCRIPTION OF THE DRAWINGS
[0033] Figure 1 It is a schematic diagram of the preparation of component A in Example 1 of the present invention.
[0034] Figure 2 It is a schematic diagram of the preparation of component B in Example 1 of the present invention.
[0035] Figure 3 It is a schematic diagram of the optical glue structure of the semi-interpenetrating double network organic gel in Example 1 of the present invention.
[0036] Figure 4 It is a loss modulus-frequency curve diagram of Comparative Examples 1, 2 and Implementation 1 of the present invention. DETAILED DESCRIPTION
[0037] The present invention will be further described in detail below in conjunction with examples, but the embodiments of the present invention are not limited thereto.
[0038] Before the mechanical and optical properties tests, the thickness of the adhesive films prepared in Examples 1-3 and Comparative Examples 1-2 after photocuring was 25 μm. When conducting the mechanical properties test, the initial adhesion was tested in accordance with the national standard GB / T4852-2002, the lasting adhesion was tested in accordance with the national standard GB / T4851-1998, and the peeling force was tested in accordance with the national standard GB / T2792-1998. When conducting the optical properties test, the adhesive film was first transferred to the optical glass, and then the transmittance and haze were tested using a Lambda 950 UV-Vis spectrophotometer and a haze meter, respectively. When conducting the room temperature rheological properties test of the optical adhesive, a DHR-2 rotational rheometer was used for testing, and the test sample specifications were 8 mm diameter × (0.8-1 mm) thickness, the temperature was 25°C, the frequency was 1 Hz, and the test mode was shear. When conducting the bending energy test, the optical glue is coated on the PET film with a coating thickness of 120μm, and then placed in an oven at 50℃ for curing for 3h, and then a clean PET film is pasted on the glue layer to make an ABA-type interlayer (the upper and lower A layers are PET films, and the middle B layer is optical glue). Then it is tested by folding with a flexibility tester (folding times 100,000 times, folding angle of 180°, speed 80 times / min), and then the PET film is observed for debonding. In the test results, excellent means no debonding, good means slight debonding, and poor means debonding.
[0039] Comparative Example 1
[0040] (1) In parts by weight, 64 parts of isooctyl acrylate, 16 parts of 2-carboxyethyl acrylate, 0.4 parts of azobisisobutyronitrile, and 160 parts of ethyl acetate were added to a four-necked flask, heated to 75° C., reacted at a speed of 80 r / min for 6 hours, and then 0.4 parts of aluminum acetylacetonate were added and stirred for 15 minutes. After the reaction was completed, the temperature was cooled to room temperature and the material was discharged to obtain component A (cross-linked network component).
[0041] (2) The adhesive solution containing only component A is coated on the release film. Then it is placed in an oven for 2 hours at 60-80°C for drying. Finally, an optical adhesive sample is obtained. The optical adhesive sample contains only a cross-linked single network.
[0042] Comparative Example 2
[0043] (1) In parts by weight, 64 parts of isooctyl acrylate, 16 parts of 2-carboxyethyl acrylate, 0.4 parts of azobisisobutyronitrile, and 160 parts of ethyl acetate were added to a four-necked flask, heated to 75° C., reacted at a speed of 80 r / min for 6 hours, and then 0.4 parts of aluminum acetylacetonate were added and stirred for 15 minutes. After the reaction was completed, the temperature was cooled to room temperature and the material was discharged to obtain component A (cross-linked network component).
[0044] (2) In parts by weight, 64 parts of isooctyl acrylate, 16 parts of hydroxyethyl acrylate, 0.4 parts of azobisisobutyronitrile, 160 parts of ethyl acetate, and 0.4 parts of dodecyl mercaptan were added to a four-necked flask, the temperature was raised to 75° C., and the reaction was carried out at a speed of 80 r / min for 6 hours. After the reaction was completed, the temperature was lowered to room temperature and the material was discharged to obtain component B (non-crosslinked network component).
[0045] (3) 40 parts of component A and 40 parts of component B are mixed evenly by weight and then coated on a release film. Then, the mixture is placed in an oven for 2 hours at 60-80° C. to obtain an optical adhesive sample. The optical adhesive sample is a semi-interpenetrating double network optical adhesive that does not contain polar small molecules.
[0046] Example 1
[0047] (1) In terms of weight, 64 parts of isooctyl acrylate, 16 parts of 2-carboxyethyl acrylate, 0.4 parts of azobisisobutyronitrile, and 160 parts of ethyl acetate were added to a four-necked flask, heated to 75°C, reacted at a speed of 80 r / min for 6 hours, and then 0.4 parts of aluminum acetylacetonate were added and stirred for 15 minutes. After the reaction was completed, the mixture was cooled to room temperature and discharged to obtain component A (cross-linked network component). The preparation process is as follows: Figure 1 shown.
[0048] (2) In terms of weight, 64 parts of isooctyl acrylate, 16 parts of hydroxyethyl acrylate, 0.4 parts of azobisisobutyronitrile, 160 parts of ethyl acetate, and 0.4 parts of dodecyl mercaptan were added to a four-necked flask, heated to 75°C, and reacted at a speed of 80 r / min for 6 hours. After the reaction was completed, the mixture was cooled to room temperature and discharged to obtain component B (non-crosslinked network component). The preparation process is as follows: Figure 2 shown.
[0049] (3) By weight, 40 parts of component A, 40 parts of component B, and 5 parts of pentanediol (component C) were mixed evenly and coated on the release film. Then, the mixture was placed in an oven for 2 hours at 60-80°C for drying. Finally, an optical adhesive sample was obtained. The optical adhesive sample is a semi-interpenetrating double network organic gel optical adhesive, and its structure is as follows: Figure 3 shown.
[0050] Example 2
[0051] (1) In parts by weight, 64 parts of isooctyl acrylate, 16 parts of 2-carboxyethyl acrylate, 0.4 parts of azobisisobutyronitrile, and 160 parts of ethyl acetate were added to a four-necked flask, heated to 75° C., reacted at a speed of 80 r / min for 6 hours, and then 0.4 parts of aluminum acetylacetonate were added and stirred for 15 minutes. After the reaction was completed, the temperature was cooled to room temperature and the material was discharged to obtain component A.
[0052] (2) In parts by weight, 64 parts of isooctyl acrylate, 16 parts of hydroxyethyl acrylate, 0.4 parts of azobisisobutyronitrile, 160 parts of ethyl acetate, and 0.4 parts of dodecyl mercaptan were added to a four-necked flask, the temperature was raised to 75° C., and the reaction was carried out at a speed of 80 r / min for 6 hours. After the reaction was completed, the temperature was lowered to room temperature and the material was discharged to obtain component B.
[0053] (3) By weight, 40 parts of component A, 40 parts of component B, and 10 parts of pentanediol (component C) were mixed evenly and coated on the release film. Then, the mixture was placed in an oven for 2 hours at 60-80°C for drying. Finally, an optical adhesive sample was obtained. The optical adhesive sample was a semi-interpenetrating double network organogel optical adhesive.
[0054] Example 3
[0055] (1) In parts by weight, 64 parts of isooctyl acrylate, 16 parts of 2-carboxyethyl acrylate, 0.4 parts of azobisisobutyronitrile, and 160 parts of ethyl acetate were added to a four-necked flask, heated to 75° C., reacted at a speed of 80 r / min for 6 hours, and then 0.4 parts of aluminum acetylacetonate were added and stirred for 15 minutes. After the reaction was completed, the temperature was cooled to room temperature and the material was discharged to obtain component A.
[0056] (2) In parts by weight, 64 parts of isooctyl acrylate, 16 parts of hydroxyethyl acrylate, 0.4 parts of azobisisobutyronitrile, 160 parts of ethyl acetate, and 0.4 parts of dodecyl mercaptan were added to a four-necked flask, the temperature was raised to 75° C., and the reaction was carried out at a speed of 80 r / min for 6 hours. After the reaction was completed, the temperature was lowered to room temperature and the material was discharged to obtain component B.
[0057] (3) By weight, 40 parts of component A, 40 parts of component B, and 15 parts of pentanediol (component C) were mixed evenly and coated on the release film. Then, the mixture was placed in an oven for 2 hours at 60-80°C for drying. Finally, an optical adhesive sample was obtained. The optical adhesive sample was a semi-interpenetrating double network organogel optical adhesive.
[0058] Example 4
[0059] (1) Preparation of component A: 64 parts of butyl acrylate, 16 parts of acrylic acid, 0.4 parts of azobisisobutyronitrile, and 160 parts of ethyl acetate were added to a four-necked flask by weight, heated to 75°C, reacted at a speed of 80 r / min for 6 hours, and then 0.4 parts of aluminum acetylacetonate were added and stirred for 15 minutes. After the reaction was completed, the temperature was cooled to room temperature and the material was discharged to obtain component A.
[0060] (2) Preparation of component B: 64 parts of butyl acrylate, 16 parts of hydroxypropyl acrylate, 0.4 parts of azobisisobutyronitrile, 160 parts of ethyl acetate, and 0.4 parts of dodecyl mercaptan were added to a four-necked flask by weight, heated to 75° C., and reacted at a speed of 80 r / min for 6 hours. After the reaction was completed, the temperature was cooled to room temperature and the material was discharged to obtain component B.
[0061] (3) Preparation of OCA optical adhesive: 50 parts of component A, 30 parts of component B, and 5 parts of 1,4-butanediol (component C) were mixed evenly by weight and then coated on the release film. Then put it in an oven for 2 hours at 60-80°C to dry. Finally, an optical adhesive sample was obtained. The optical adhesive sample is a semi-interpenetrating double network organogel optical adhesive.
[0062] Example 5
[0063] (1) Preparation of component A: 64 parts of butyl acrylate, 16 parts of acrylic acid, 0.4 parts of azobisisobutyronitrile, and 160 parts of ethyl acetate were added to a four-necked flask by weight, heated to 75°C, reacted at a speed of 80 r / min for 6 hours, and then 0.4 parts of aluminum acetylacetonate were added and stirred for 15 minutes. After the reaction was completed, the temperature was cooled to room temperature and the material was discharged to obtain component A.
[0064] (2) Preparation of component B: 64 parts of butyl acrylate, 16 parts of hydroxypropyl acrylate, 0.4 parts of azobisisobutyronitrile, 160 parts of ethyl acetate, and 0.4 parts of dodecyl mercaptan were added to a four-necked flask by weight, heated to 75° C., and reacted at a speed of 80 r / min for 6 hours. After the reaction was completed, the temperature was cooled to room temperature and the material was discharged to obtain component B.
[0065] (3) Preparation of OCA optical adhesive: 50 parts of component A, 30 parts of component B, and 20 parts of polypropylene glycol (Mn=200) (component C) were mixed evenly by weight and coated on the release film. Then put it in an oven for 2 hours and dried at 60-80°C. Finally, an optical adhesive sample was obtained. The optical adhesive sample is a semi-interpenetrating double network organic gel optical adhesive.
[0066] Example 6
[0067] (1) Preparation of component A: 64 parts of isooctyl acrylate, 16 parts of 2-carboxyethyl acrylate, 0.4 parts of azobisisobutyronitrile, and 160 parts of ethyl acetate were added to a four-necked flask by weight, heated to 75°C, reacted at a speed of 80 r / min for 6 hours, and then 0.4 parts of aluminum acetylacetonate were added and stirred for 15 minutes. After the reaction was completed, the temperature was cooled to room temperature and the material was discharged to obtain component A.
[0068] (2) Preparation of component B: 64 parts of isooctyl acrylate, 16 parts of hydroxybutyl acrylate, 0.4 parts of azobisisobutyronitrile, 160 parts of ethyl acetate, and 0.4 parts of dodecyl mercaptan were added to a four-necked flask by weight, heated to 75° C., and reacted at a speed of 80 r / min for 6 hours. After the reaction was completed, the temperature was cooled to room temperature and the material was discharged to obtain component B.
[0069] (3) Preparation of OCA optical adhesive: 30 parts of component A, 50 parts of component B, and 10 parts of amyl alcohol (component C) were mixed evenly by weight and then coated on the release film. Then put it in an oven for 2 hours at 60-80°C to dry. Finally, an optical adhesive sample was obtained. The optical adhesive sample is a semi-interpenetrating double network organic gel optical adhesive.
[0070] Example 7
[0071] (1) Preparation of component A: By weight, 48 parts of isooctyl acrylate, 16 parts of methyl acrylate, 16 parts of 2-carboxyethyl acrylate, 0.4 parts of azobisisobutyronitrile, and 160 parts of ethyl acetate were added to a four-necked flask, heated to 75°C, reacted at a speed of 80 r / min for 6 hours, and then 0.4 parts of aluminum acetylacetonate were added and stirred for 15 minutes. After the reaction was completed, the temperature was cooled to room temperature and the material was discharged to obtain component A.
[0072] (2) Preparation of component B: 48 parts of isooctyl acrylate, 16 parts of methyl acrylate, 16 parts of hydroxypropyl acrylate, 0.4 parts of azobisisobutyronitrile, 160 parts of ethyl acetate, and 0.4 parts of dodecyl mercaptan were added to a four-necked flask, heated to 75°C, and reacted at a speed of 80 r / min for 6 hours. After the reaction was completed, the temperature was cooled to room temperature and the material was discharged to obtain component B.
[0073] (3) Preparation of OCA optical adhesive: 40 parts of component A, 40 parts of component B, and 5 parts of isooctyl alcohol (component C) were mixed evenly by weight and then coated on the release film. Then put it in an oven for 2 hours at 60-80°C for drying. Finally, an optical adhesive sample was obtained. The optical adhesive sample is a semi-interpenetrating double network organogel optical adhesive.
[0074] Example 8
[0075] (1) Preparation of component A: 64 parts of isooctyl acrylate, 16 parts of 2-carboxyethyl acrylate, 0.4 parts of azobisisobutyronitrile, and 160 parts of ethyl acetate were added to a four-necked flask by weight, heated to 75°C, reacted at a speed of 80 r / min for 6 hours, and then 0.4 parts of aluminum acetylacetonate were added and stirred for 15 minutes. After the reaction was completed, the temperature was cooled to room temperature and the material was discharged to obtain component A.
[0076] (2) Preparation of component B: 64 parts of isooctyl acrylate, 16 parts of hydroxybutyl acrylate, 0.4 parts of azobisisobutyronitrile, 160 parts of ethanol, and 0.4 parts of dodecyl mercaptan were added to a four-necked flask by weight, heated to 75° C., and reacted at a speed of 80 r / min for 6 hours. After the reaction was completed, the temperature was cooled to room temperature and the material was discharged to obtain component B.
[0077] (3) Preparation of OCA optical adhesive: 40 parts of component A, 40 parts of component B, and 10 parts of propylene glycol (component C) were mixed evenly by weight and then coated on the release film. Then put it in an oven for 2 hours at 60-80°C to dry. Finally, an optical adhesive sample was obtained. The optical adhesive sample is a semi-interpenetrating double network organic gel optical adhesive.
[0078] Example 9
[0079] (1) Preparation of component A: 64 parts of isooctyl acrylate, 16 parts of 2-carboxyethyl acrylate, 0.4 parts of azobisisobutyronitrile, and 160 parts of ethanol were added to a four-necked flask by weight, heated to 75°C, reacted at a speed of 80 r / min for 6 hours, and then 0.4 parts of aluminum acetylacetonate were added and stirred for 15 minutes. After the reaction was completed, the temperature was cooled to room temperature and the material was discharged to obtain component A.
[0080] (2) Preparation of component B: 60 parts by weight of isooctyl acrylate, 20 parts by weight of hydroxyethyl acrylate, 0.4 parts by weight of azobisisobutyronitrile, 160 parts by weight of ethyl acetate, and 0.4 parts by weight of dodecyl mercaptan were added to a four-necked flask, heated to 75° C., and reacted at a speed of 80 r / min for 6 hours. After the reaction was completed, the temperature was cooled to room temperature and the material was discharged to obtain component B.
[0081] (3) Preparation of OCA optical adhesive: 50 parts of component A, 50 parts of component B, and 15 parts of octanediol (component C) were mixed evenly by weight and then coated on the release film. Then put it in an oven for 2 hours at 60-80°C to dry. Finally, an optical adhesive sample was obtained. The optical adhesive sample is a semi-interpenetrating double network organogel optical adhesive.
[0082] Analysis of optical adhesive transmittance, bonding, mechanics and folding resistance
[0083] According to the above test method, comprehensive performance analysis was performed on samples of Examples 1-9 and Comparative Examples 1-2; the results are shown in Table 1:
[0084] Table 1. Performance test table of samples of Examples 1-9 and Comparative Examples 1-2
[0085]
[0086]
[0087] From the data in Table 1, we can see that: First, the silicone-modified acrylate OCA optical adhesive prepared in Examples 1-9 of the present application has a moderate initial adhesion (6-8 balls) due to the moderate ratio of soft and hard monomers. This value meets the ideal value for high-end OCA optical adhesive films internationally and meets industry requirements. In Examples 1-9, due to the addition of polar small molecules, the cohesive energy between molecular chains is reduced, which plays a role similar to that of a plasticizer. Therefore, the holding force of Examples 1-9 is lower than that of Comparative Examples 1 and 2, but it is still greater than 100h, which fully meets the requirements. As for the peeling force, the polarity of the colloid is enhanced due to the introduction of polar small molecules. Therefore, as the content of polar small molecules increases, the peeling strength shows an upward trend.
[0088] The transmittance of the OCA optical adhesive films prepared in Examples 1-9 is greater than 99%, and the haze value does not exceed 0.2%; this is mainly because all the raw materials are colorless and do not contain color-developing groups, and these monomers will not change color after free radical polymerization. In addition, since the raw materials used basically do not contain water molecules, there is very little water vapor in the film; and since hydroxyl-containing acrylate monomers are added to the formula, this will make the very little water vapor evenly dispersed without causing the formation of cloud points. Compared with Chinese invention patent application CN113025240A, the optical adhesive of this application has better light transmittance efficiency and lower haze, and has a better display effect.
[0089] The OCA optical adhesives prepared in Examples 1-9 are all semi-interpenetrating double network organogel systems, while Comparative Example 1 is a single network system, and Comparative Example 2 is a semi-interpenetrating double network system, and the folding performance of Examples 1-9 is better than that of Comparative Examples 1 and 2. This is because the cross-linked network in the semi-interpenetrating double network organogel system can provide effective skeleton support, prevent the colloid from undergoing irreversible deformation during folding, ensure that the colloid has good resilience, and make it have excellent anti-fatigue performance during the folding process; while the uncross-linked network is almost all linear macromolecules, which can provide a certain wetting ability for the colloid and enhance the bonding with the substrate; the polar small molecules further enhance the polarity of the substrate, so that a large number of reversible hydrogen bonds are formed between the molecules, and these reversible hydrogen bonds can absorb a large amount of energy in the process of being destroyed and rebuilt, providing the colloid with good energy dissipation capacity, thereby further reducing the generation of folding stress. Figure 4The loss modulus-frequency curves of Examples 1, 2 and Implementation 1 are shown in the figure. The loss modulus of Implementation 1 is the largest, followed by Example 2, and the smallest of Example 1. This shows that Example 1 has the best energy dissipation capacity and can effectively convert the stress and energy generated during the folding process into heat for dissipation, thereby preventing the colloid from being damaged during the folding process. This further proves that the optical adhesive of this application has better folding resistance. Compared with the Chinese invention patent CN110776855B, this patent has only a single network system, with fewer reversible structures, and cannot effectively absorb stress during the folding process, so it cannot cope with the folding process of more than 100,000 times in the long-term use of the folding display device.
[0090] To sum up, compared with the optical pressure-sensitive adhesive used for display devices in the prior art, this application is the first to effectively improve the folding resistance of the optical adhesive by constructing a semi-interpenetrating double network system and an organic gel system. The optical adhesive of this application has the advantages of both good bonding properties and folding resistance, which makes it have broad application prospects in foldable flexible electronic display devices.
[0091] The above embodiments are preferred implementation modes of the present invention, but the implementation modes of the present invention are not limited to the embodiments. Any other changes, modifications, substitutions, combinations, and simplifications made without departing from the spirit and principles of the present invention shall be equivalent replacement modes and shall be included in the protection scope of the present invention.
Claims
1. A method for preparing a semi-interpenetrating double network organic gel OCA optical adhesive for folding display devices, characterized in that: The following steps are involved: Preparation of a cross-linked network component: 20 to 80 parts of an alkyl acrylate monomer, 5 to 20 parts of an acrylic acid monomer with a carboxyl group, 0.05 to 1 part of a cross-linking agent, 0.1 to 2 parts of a thermal initiator, and 90 to 240 parts of a solvent are added to a reaction container, the temperature is raised to 70 to 75° C., and the reaction is carried out at a speed of 70 to 80 r / min for 6 to 8 hours; after the reaction is completed, the temperature is lowered to room temperature and the material is discharged to obtain a cross-linked network component; Preparation of non-crosslinked network components: 20-80 parts of alkyl acrylate monomers, 5-20 parts of hydroxy acrylate monomers, 0.1-2 parts of thermal initiators, and 0.5-1 parts of chain transfer agents are added to a reaction container, heated to 70-75° C., and reacted at a speed of 70-80 r / min for 6-8 hours; after the reaction is completed, the reaction is cooled to room temperature and discharged to obtain a non-crosslinked network component; Preparation of semi-interpenetrating double network organogel: 20 to 40 parts of cross-linked network components, 20 to 40 parts of non-cross-linked network components and 1 to 40 parts of polar small molecules are mixed evenly and then coated on a release film, and then placed in an oven and dried at 60 to 80° C. to obtain a semi-interpenetrating double network organogel OCA optical adhesive; The polar small molecule is at least one of ethanol, n-propanol, isopropanol, n-butanol, isobutanol, n-pentanol, isopentanol, n-hexanol, heptanol, octanol, isooctyl alcohol, ethylene glycol, propylene glycol, butanediol, pentanediol, hexanediol, heptanediol, octanediol, glycerol, pentaerythritol, polyethylene glycol, and polypropylene glycol.
2. The method for preparing the semi-interpenetrating double network organogel OCA optical adhesive for folding display devices according to claim 1, characterized in that: The alkyl acrylate is at least one of methyl acrylate, ethyl acrylate, isopropyl acrylate, isoamyl acrylate, sec-butyl acrylate, n-butyl acrylate, isobornyl acrylate, 2-methylbutyl acrylate, 4-methyl-2-pentyl acrylate, 2-ethylhexyl acrylate, and isooctyl acrylate.
3. The method for preparing the semi-interpenetrating double network organic gel OCA optical adhesive for folding display devices according to claim 1, characterized in that: The carboxyl-containing acrylic monomer is at least one of acrylic acid, methacrylic acid, and 2-carboxyethyl acrylate.
4. The method for preparing the semi-interpenetrating double network organogel OCA optical adhesive for folding display devices according to claim 1, characterized in that: The crosslinking agent is at least one of aluminum acetylacetonate, aziridine, ethylene glycol di(meth)acrylate, diethylene glycol di(meth)acrylate, triethylene glycol di(meth)acrylate, tetraethylene glycol di(meth)acrylate, 1,4-butanediol di(meth)acrylate, 1,6-hexanediol di(meth)acrylate, 1,6-hexanediol diacrylate, trimethylolpropane triacrylate, dipropylene glycol diacrylate, tripropylene glycol diacrylate, cyclohexanedimethanol di(meth)acrylate, alkoxylated cyclohexanedimethanol diacrylate, ethoxylated bisphenol A di(meth)acrylate, neopentyl glycol diacrylate, polyethylene glycol di(meth)acrylate, polypropylene glycol di(meth)acrylate and urethane di(meth)acrylate.
5. The method for preparing the semi-interpenetrating double network organic gel OCA optical adhesive for folding display devices according to claim 1, characterized in that: The thermal initiator is at least one of benzoyl peroxide and azobisisobutyronitrile.
6. The method for preparing the semi-interpenetrating double network organogel OCA optical adhesive for folding display devices according to claim 1, characterized in that: The hydroxy acrylate is at least one of hydroxyethyl acrylate, hydroxypropyl acrylate, hydroxyethyl methacrylate and hydroxypropyl methacrylate.
7. The method for preparing the semi-interpenetrating double network organogel OCA optical adhesive for foldable display devices according to claim 1, characterized in that: The chain transfer agent is at least one of dodecyl mercaptan and tert-dodecyl mercaptan.
8. The method for preparing the semi-interpenetrating double network organogel OCA optical adhesive for foldable display devices according to claim 1, characterized in that: The solvent is at least one of acetone, ethyl acetate, n-butyl acetate, n-hexane, n-heptane, benzene, toluene, methyl ethyl ketone, methyl isobutyl ketone, cyclohexane, methylcyclohexane and anhydrous ethanol.
9. A semi-interpenetrating double network organic gel OCA optical adhesive for folding display devices, characterized in that: The invention comprises a mixture coated on a release film; the mixture comprises 20 to 40 parts of a cross-linked network component, 20 to 40 parts of a non-cross-linked network component and 1 to 40 parts of a polar small molecule; The cross-linked network component is prepared by reacting 20 to 80 parts of alkyl acrylate monomer, 5 to 20 parts of acrylic acid monomer with carboxyl group, 0.05 to 1 part of cross-linking agent, 0.1 to 2 parts of thermal initiator and 90 to 240 parts of solvent; The non-crosslinked network component comprises 20 to 80 parts of alkyl acrylate monomers, 5 to 20 parts of hydroxy acrylate monomers, 0.1 to 2 parts of thermal initiator, and 0.5 to 1 part of chain transfer agent; The polar small molecule is at least one of ethanol, n-propanol, isopropanol, n-butanol, isobutanol, n-pentanol, isopentanol, n-hexanol, heptanol, octanol, isooctyl alcohol, ethylene glycol, propylene glycol, butanediol, pentanediol, hexanediol, heptanediol, octanediol, glycerol, pentaerythritol, polyethylene glycol, and polypropylene glycol.
10. A foldable display device, characterized in that: Including the semi-interpenetrating double network organic gel OCA optical adhesive used in folding display devices as described in claim 9.
Citation Information
Patent Citations
Pressure-sensitive adhesive compositions, polarizers and liquid crystal displays comprising the same
CN101910345A
High-performance OCA (Optical Clear Adhesive) for folding screen and preparation method of high-performance OCA
CN114907781A
Preparation method of optical OCA (Optical Clear Adhesive) and application of optical OCA in folding screen of mobile phone
CN115895467A
Pressure-sensitive adhesive compositions, a polarizer and a liquid crystal display comprising the same
KR1020090111261A
Interpenetrating Networks With Covalent and Ionic Crosslinks
US20150038613A1